DIVERSI SEBAGAI ALTERNATIF PENYELESAIAN PIDANA ANAK PERSPEKTIF UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK - Kholil, Abdul (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
Diversion was born in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, its existence is an alternative to resolving cases faced by children, deliberation to obtain justice for all parties is the main objective of Diversion, the important point in this article is related to how Diversion becomes restorative justice as a resolution of criminal problems without using court decisions based on normative legal research using existing regulations, Children are national assets whose involvement in criminal matters should be avoided, the government with all its authority has made regulations on Diversion which must be carried out at all levels of cases, both the Police, Prosecutors and the Courts, the lack of socialization of this law should be a concern for all parties so that all children get the rights that have been granted by law.